2015
DOI: 10.1155/2015/350410
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and Antimigratory Activities of Phenolic Compounds fromDendrobium brymerianum

Abstract: Chromatographic separation of a methanol extract prepared from the whole plant of Dendrobium brymerianum led to the isolation of eight phenolic compounds. Among the isolated compounds (1–8), moscatilin (1), gigantol (3), lusianthridin (4), and dendroflorin (6) showed appreciable cytotoxicity against human lung cancer cell lines with IC50 values of 196.7, 23.4, 65.0, and 125.8 μg/mL, respectively, and exhibited antimigratory property at nontoxic concentrations. This study is the first report on the biological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 23 publications
4
29
0
1
Order By: Relevance
“…Boonchoo Sritularak in a previous study [7][8][9] . 1,1-Diphenyl-2-picrylhydrazyl (DPPH), 2,4,6-tripyridyl-s-triazine (TPTZ), and 6-hydroxy-2,5,7,8-tetramethylchromane-2-carboxylic acid (Trolox) were purchased from Sigma-Aldrich Chemical Co. (St. Louis, MO, USA).…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Boonchoo Sritularak in a previous study [7][8][9] . 1,1-Diphenyl-2-picrylhydrazyl (DPPH), 2,4,6-tripyridyl-s-triazine (TPTZ), and 6-hydroxy-2,5,7,8-tetramethylchromane-2-carboxylic acid (Trolox) were purchased from Sigma-Aldrich Chemical Co. (St. Louis, MO, USA).…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…Pharmacological studies have demonstrated that moscatilin has antimutagenic activity in human colorectal cancer cells and anti-angiogenesis activity was seen in vitro and in vivo tests 5,6 . Bibenzyl and phenanthrene compounds, such as gigantol, moscatilin and lusianthridin, exhibit anti-migratory activities and can inhibit filopodia formation in nonsmall cell lung cancer cells [7][8][9] . In addition, the antiplatelet aggregating activity of moscatilin, homoeriodictyol and gigantol was reported in an in vitro test 10 .…”
Section: Introductionmentioning
confidence: 99%
“…[80] Other authors found that several phenolic constituents isolated from D. nobile, together with moscatilin (40), gigantol (44), lusianthridin (a dihydrophenanthrene), and dendroflorin showed cytotoxicity against human lung cancer cell lines with IC 50 values of 196.7, 23.4, 65.0, and 125.8 lg/ml, respectively, and exhibited anti-migratory property at nontoxic concentrations. [81] More recently, 44 showed promising activity against cancer cells due to suppression of epithelial to mesenchymal transition (EMT) in non-small cell lung cancer cells (H460). Western blot analysis has revealed that gigantol (44) attenuates the activity of ATP-dependent tyrosine kinase (AKT), thereby inhibiting the expression of the major EMT transcription factor (Slug), by both decreasing its transcription and increasing its degradation.…”
Section: Dihydrostilbenoids and Related Derivativesmentioning
confidence: 99%
“…Other authors found that several phenolic constituents isolated from D . nobile , together with moscatilin ( 40 ), gigantol ( 44 ), lusianthridin (a dihydrophenanthrene), and dendroflorin showed cytotoxicity against human lung cancer cell lines with IC 50 values of 196.7, 23.4, 65.0, and 125.8 μg/ml, respectively, and exhibited anti‐migratory property at nontoxic concentrations . More recently, 44 showed promising activity against cancer cells due to suppression of epithelial to mesenchymal transition (EMT) in non‐small cell lung cancer cells (H460).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have revealed that natural products isolated from Dendrobium species possess anticancer properties including anti-proliferation, anti-migration, anti-metastasis, and apoptotic induction in lung cancer (108)(109)(110). Gigantol, a bibenzyl phenolic compound derived from several medicinal orchids, has been shown to inhibit proliferation, migration, EMT and CSC phenotype in lung cancer cells (111)(112)(113)(114). At non-toxic doses (below 20 μM), gigantol isolated from Dendrobium draconis could suppress tumor spheroid formation and decrease lung CSC marker proteins, including CD133 and ALDH1A1, in non-small-cell lung cancer NCI-H460 cells (112).…”
Section: Natural Product Targeting Lung Cancer Stem Cellsmentioning
confidence: 99%